Gas phase glycerol dehydration over H-ZSM-5 zeolite modified by alkaline treatment with Na2CO3 - Lago, Camila Desire (2018)
Modified H-ZSM-5 zeolite catalysts were studied for the dehydration of glycerol to acrolein in gas phase. The modifications were made by alkaline treatment using Na2CO3 solutions in different concentrations, followed by consecutive ion exchanges with NH4NO3 solution in order to recover the acidic form of the materials. The mild conditions selected (alkali concentrations, time and temperature) allowed to preserve the crystallinity and framework characteristic in the zeolite, selectively removing silicon while maintaining practically all the aluminum content. This process has important advantages over the alkaline treatment with NaOH (at an equivalent pH), such as high selectivity to remove silicon instead of aluminum, and in addition the yield of synthesized material respect to the initial mass is markedly higher (80% vs 50%). This treatment with Na2CO3 solutions leads to multiple positive effects as: increments in the mesoporosity and external surface area; and changes in the nature and accessibility to the acid active sites. The catalytic activity and selectivity were greatly improved. Further, the deactivation by coke deposition was attenuated.